2 - Financing Higher Education through Value Added Tax: A Review of the Contribution of the Ghana Education Trust Fund (GETFund) in Fulfilment of the Objectives of Act 581 - Francis Atuahene (Journal of Higher Education in Africa, 2009)
The Ghana Education Trust Fund (GETFund), funded by a percentage of the national Value Added Tax, has had as its purpose, since its establish- ment in 2000, the enhancement of primary, secondary and particularly terti- ary education. This research paper examines the perceptions of key stakeholders as to the contributions, thus far, of the GETFund in address- ing principal objectives and challenges such as infrastructural develop- ment, research and faculty development, the promotion of technology, mathematics and scientific education, student access and gender equity. Through the lens of stakeholders, recommendations are offered for poten- tial enhancements to the GETFund and for its adaptation to other national circumstances. The analysis of this paper is primarily a combination of the perceptions of stakeholders such as vice-chancellors, pro-vice-chancel- lors, registrars, principals, legislators, student leaders, public officials, etc., as well as available GETFund disbursement formulae and policy papers from 2001 to 2006. The outcome of this study is a series of judgements on the contribution of the GETFund compared to prior government objectives and recommendations relevant to the adaptation of the programme in other nations.